Politično-geografski dejavniki selektivnosti notranjih (medrepubliških) migracij v SFRJ (1945–1991) kot primer psevdoprostovoljnih migracij, s poudarkom na Bosni in Hercegovini - Josipovič, Damir (Dve domovini, 2025)
Internal migrations were relatively strong during the pre–World War II Yugoslav Kingdom; however, in socialist Yugoslavia, they significantly intensified and changed in direction and structure. Three periods of the inter-republic migrations can be roughly discerned: a) the period of pan-Yugoslav consolidation (1945–1956); b) the period of pan-Yugoslav enthusiasm (1956–1974); and c) the period of supranational disintegration (1974–1991). The so-called pseudo-voluntary migration marks each of them. The article explains the basis, structure, and causality of intra-Yugoslav migrations as well as the selectivity of migration based on ethnicity, with a special emphasis on Bosnia and Herzegovina.
Keywords: ethnic selectivity; etnična selektivnost; inter-republic migration; Jugoslavia; Jugoslavija; Jugoslavs; Jugoslovani; medrepubliške migracije; migracije; migration; pseudo-voluntary migration; psevdoprostovoljne migracije